Do human embryos have the ability of self-correction? - Raoul Orvieto; Chen Shimon; Shlomit Rienstein; Anat Jonish-Grossman; Hagit Shani; Adva Aizer (BMC, 2020)
Abstract Human embryogenesis frequently coinciding with cell division mistakes contributing to pervasive embryonic aneuploidy/mosaicism. While embryo self-correction was elegantly demonstrated in mouse models, human studies are lacking. Here we are witness to human embryos ability to eliminate/expel abnormal blastomeres as cell debris/fragments. Each blastocyst and its corresponding debris were separated and underwent whole genome amplification. Seven of the 11 pairs of blastocysts and their corresponding cell debris/fragments revealed discordant results. Of the 9 euploid blastocysts, four showed euploid debris, while in the others, the debris were aneuploid. In the remaining pairs, the debris showed additional aneuploidy to those presented by their corresponding blastocyst. The observed ability of human embryos to self-correction doubts many invasive and non-invasive preimplantation testing for aneuploidy at the blastocyst stage, rendering high rate of false positive (discarding "good" embryos) by identifying the cell-free DNA originated from the expelled cell debris, as aneuploidy/mosaic blastocyst.